Effects of High-Quality Aromatic Rice Varieties on the Fitness of the Striped Stem Borer, Chilo suppressalis (Walker) in Central China - Xue-zhu DU; Yong WANG; Long-jia CHEN; Chuan-hua PENG; Wei-hua MA; Chao-liang LEI (Journal of Integrative Agriculture, 2013)
The striped stem borer (SSB), Chilo suppressalis (Walker) (Lepidoptera: Pyralidae), is a major pest of rice in China. Variation in host-plant quality may affect the body size of herbivorous insects, which in turn, can determine their life-history parameters such as survival, fecundity and fitness. In this study, we tested the effects of high-quality aromatic rice varieties on the fitness of SSB in China. Results showed that 1st instar larvae had higher penetrating rates and survival rates on the high-quality aromatic rice varieties (EX-1 and WX-988) than that on the non-aromatic rice varieties (EZ-5 and LYP-9). In addition, shorter developmental periods, greater female pupal weights and higher of other life-history parameters (hatching rate, pupation rate, eclosion rate and increase index) were found on the high-quality aromatic rice varieties, although only female pupal weight showed a significant difference between the two varieties. The highest dead heart rate was found on the aromatic rice variety of EX-1. These results indicate that SSB sustains a lower fitness cost when consuming the high-quality aromatic rice varieties (EX-1 and WX-988) than on the non-aromatic rice varieties (EZ-5 and LYP-9) in Central China.